# Math

posted by on .

x-4 multiplied by x-3 equals what? 2x-1 multiplied by x-3 equals what?

I tried doing each problem each time and whenever it is in fraction form since that is how it is suppose to be written, it doesn't look right. What could I be doing wrong?

• Math - ,

you mean:
(x-4)(x-3)=?
and
(2x-1)(x-3)=?
When multiplying binomials, we use FOIL or First Outside Inside Last to express the product as a sum of terms.

(x-4)(x-3)
First-multiply first two terms of the two binomials.
Outside-multiply the first terms of the first binomial with the last term of the second binomial.
Inside-multiply the last term of the first binomial and the first term of the second binomial
last-multiply the last term of both binomials.

then combine like terms
x^2=first
-3x=outside
-4x=inside
12=last

x^2-3x-4x+12=x^2-7x+12
(2x-1)(x-3)=2x^2-6x-x+3=2x^2-7x+3
Hope this helped. Peace.

### Answer This Question

 First Name: School Subject: Answer:

### Related Questions

More Related Questions

Post a New Question